Ocorrencia da Marreca Cabocla Dendrocygna autumnalis no noroeste do Rio Grande do Sul, Brasil - Guadagnin, Demétrio (1995)
Occurrence of Dendrocygna autumnalis in Northwest Rio Grande do Sul, Brazil. The first undoubted record of the species in the State, at 56° 08' W e 28° 46' S, is given, based on visual observation with slide documentation of two flocks, totalling 236 birds, in may 1991.